دور القانون الدولي الإنساني في حماية البيئة: دراسة مقارنة - زين، زكريا عبدالوهاب محمد (مركز جيل البحث العلمي, 2018)
تناول هذا البحث دور القانون الدولي الإنساني في حماية البيئة، وقد استعرض البحث التعريف بالبيئة وأهميتها وضرورة حمايتها وذلك من خلال المبحث الأول. أما المبحث الثاني فقد بين حماية البيئة في إطار الاتفاقيات الدولية المختلفة، ودور المنظمات الدولية في حماية البيئة. أما المبحث الثالث فقد وضح تعريف القانون الدولي الإنساني، كقانون له جذور تاريخية قديمة، ومن ثم تناول بعضا من اهتمام الشريعة الإسلامية بالبيئية أثناء النزاعات المسلحة، وكذلك بين نهج القانون الدولي الإنساني في هذا الإطار، وقد اهتم هذا المبحث أيضا بتوضيح دور المصادر المباشرة وغير المباشرة للقانون الدولي الإنساني في حماية البيئة.
This research takes the role of humanitarian law in the environment protection; the research displays the acquaintance of environment, its importance and the necessity of its protection that is included in the first chapter. The second chapter explains the environment protection in the framework of the deferent environmental agreements, the role of international organizations in the environment protection. The second chapter illustrates the definition of the environmental humanitarian law as a law which has and old historical roots, then it lakes the interest of Islamic jurisprudence of the environment during the armed conflicts, also explains the approach of international humanitarian law in this framework, the chapter also interests in illustration of the direct source rok and indirect of international humanitarian law in the environment protection.
Keywords: البيئة -- حماية البيئة -- الاتفاقيات الدولية -- النزاعات المسلحة -- المنظمات الدولية -- القانون الدولي الإنساني